CARACTERÍSTICAS BROMATOLÓGICAS E DIGESTIBILIDADE DE HÍBRIDOS DE MILHO COM DIFERENTES TEXTURAS DE GRÃOS - Rossi, Evandrei Santos (2014)
In determining the quality of corn hybrid for silage utilization, the knowledge of bromatological analysis as well as digestibility of dry matter are important steps to assign quality of a genotype. The objective of this study was to evaluate the vitreousness in commercial corn hybrids with hard and dented grains, and studying the effect of this characteristic on agronomic behavior, nutritional value, and dry matter degradability of grains and forage harvest at the point of silage in different cultivation places and studying the microstructure of the starch granules. Twelve commercial corn hybrids were evaluated, being 6 with hard grains e 6 with dent grains. The treatments were evaluated in two places represented by Guarapuava and Laranjeiras do Sul both on Paraná State. The harvest for forage quality analysis was performed 20 cm above ground at the ¾ of the milk line stage in grain. The characteristics evaluated were: Grain yield, green matter yield, dry matter yield, grain yield at the silage point, degradable dry matter yield, vitreousness, in situ digestibility of grain and forage, neutral detergent fiber of grains and forage, acid detergent fiber of grains and forage, crude protein of grains and forage, mineral matter of grains and forage, dry matter of forage and grains. There was significant effect for sources of variation: place, hybrid and hybrid x place for most of the evaluated traits. The hybrids AG 8041PRO and 1572PRO were stood when compared with others hybrids for forage production of the whole plant. The group dent hybrids outperformed the group of hard hybrids, with best degradability of the grains and forage of the whole plant, associated with higher yield degradable dry matter. There was negative correlation between vitreousness digestibility of grain and forage and can be a used as factor of criterion when selecting genotypes for silage. The place in Guarapuava outperformed from Laranjeiras do Sul with better performance for agronomic traits demonstrating the influence of the environment.